Organic matter identifies the nano-mechanical properties of native soil aggregates. Issue 2 (14th December 2017) - Gazze, S. A.; Hallin, I.; Quinn, G.; Dudley, E.; Matthews, G. P.; Rees, P.; van Keulen, G.; Doerr, S. H.; Francis, L. W.
Abstract : Variations at the nanoscale in soil and organic matter distribution are critical to understanding the factors involved in soil composition and turnover. Atomic Force Microscopy describes soil physical and topographical properties at the nanoscale, and thus represents an important tool in soil nanoscience. Abstract : Localized variations at the nanoscale in soil aggregates and in the spatial organisation of soil organic matter (SOM) are critical to understanding the factors involved in soil composition and turnover. However soil nanoscience has been hampered by the lack of suitable methods to determine soil biophysical properties at nanometre spatial resolution with minimal sample preparation. Here we introduce for the first time an Atomic Force Microscopy (AFM)-based Quantitative Nano-Mechanical mapping (QNM) approach that allows the characterisation of the role of SOM in controlling surface nano-mechanical properties of soil aggregates. SOM coverage resulted in an increased roughness and surface variability of soil, as well as in decreased stiffness and adhesive properties. The latter also correlates with nano- to macro-wettability features as determined by contact angle measurements and Water Drop Penetration Time (WDPT) testing. AFM thus represents an ideal quantitative tool to complement existing techniques within the emerging field of soil nanoscience.